54.6k views
0 votes
Prove that u(x) := e* (x COS Y – ysiny) is harmonic and find a conjugate function of u.

User Ckv
by
5.5k points

1 Answer

5 votes

Answer:


u(x)=\ =\ e^x(xcosy\ -\ ysiny)\ \textrm{is harmonic.}


\textrm{conjugate function},\ v\ =\ 2e^x(xsiny\ +\ ycosy)\ +\ c

Explanation:

As given in question,


  • u(x)\ =\ e^x(xcosy\ -\ ysiny)


=\ e^x.xcosy\ -\ e^x.ysiny


=>\ u'_x(x)\ =\ e^x.cosy\ +\ xe^xcosy\ -\ ye^xsiny\\\\=>\ u''_x(x)\ =\ e^xcosy+e^xcosy+xe^xcosy-e^xysiny\\\\=>\ u'_y(x)\ =\ -e^x.xsiny\ -\ e^xsiny\ -\ e^x.ycosy\\\\=>\ u''_y(x)\ =\ -xe^xcosy\ -\ 2e^xcosy\ +\ e^x.ysiny

For a system to be harmonic,


(\partial^2 u)/(\partial x^2)\ +\ (\partial^2 u)/(\partial y^2)\ =\ 0

From the above calculated value we can see that


(\partial^2 u)/(\partial x^2)\ +\ (\partial^2 u)/(\partial y^2)


=\ e^xcosy+e^xcosy+xe^xcosy-e^xysiny\ -\ xe^xcosy\ -\ 2e^xcosy\ +\ e^x.ysiny

= 0

So, given function u(x) is harmonic.

Now to find conjugate function of u,


dv\ =\ (\partial v)/(\partial x).dx\ +\ (\partial v)/(\partial y).dy

According to Cauchy-Riemen Equation,


(\partial u)/(\partial x)\ =\ (\partial v)/(\partial y)\\\\(\partial u)/(\partial y)\ =\ -(\partial v)/(\partial x)

So, we4 can write the above equation as,


dv\ =\ -(\partial u)/(\partial y)dx\ +\ (\partial u)/(\partial x)dy

on putting the values, we have


dv\ =\ -(-e^x.xsiny\ -\ e^xsiny\ -\ e^x.ycosy)dx\ +\ (e^x.cosy\ +\ xe^xcosy\ -\ ye^xsiny)dy

on integrating both side, we get


\int{dv}\ =\ \int{e^x.xsiny\ +\ e^xsiny\ +\ e^x.ycosy)dx}\ +\ \int{(e^x.cosy\ +\ xe^xcosy\ -\ ye^xsiny)dy}


=>\ v\ =\ 2xe^xsiny\ +\ 2ye^xcosy\ +\ c


=\ 2e^x(xsiny\ +\ ycosy)\ +\ c

hence, the conjugate equation can be given by


v\ =\ 2e^x(xsiny\ +\ ycosy)\ +\ c

User Fge
by
5.6k points